ANALISIS PENERAPAN ALGORITMA C4.5 UNTUK MENGIDENTIFIKASI KELANCARAN KREDIT NASABAH PADA CU. DOSNITAHI PINANG SORI - Saputra, Muhardi; Sinaga, Indah Putri Lestari; Sinaga, Wendy (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
CU cooperative. Donsitahi Pinang Sori is a business unit engaged in savings and loan services that are protected under Law Number 25 of 1992. Savings and loans that are often in demand by customers are cash savings and loans. The problem that occurs is that bad credit often occurs on cash loan customers. Various reasons put forward by customers in arrears of payment. This is very detrimental to the cooperative. For this reason, an analysis of the relationship between education, employment, number of dependents, salary, home ownership and monthly tenure is needed for prospective customers in order to form a classification / grouping of prospective customers' backgrounds so that the company can consider whether to approve or reject the application. Method analysis using the c4.5 algorithm. The results obtained from the 1001 processing data are if the number of dependents is large but the salary is large then it will be in the nature of current credit.